2019
DOI: 10.1002/cld.813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Infection in Cirrhosis: Organ Failures and Acute‐on‐Chronic Liver Failure

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-3-reading-wong a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-3-interview-wong the interview with the author https://www.wileyhealthlearning.com/Activity/6904687/disclaimerspopup.aspx questions and earn CME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In general, pro-inflammatory immune responses are thought to drive progressive CLD through bystander cell damage and activation of fibrogenic and hepatocarcinogenic pathways. Anti-inflammatory responses may counter these injurious pro-inflammatory responses and slow pathogenesis, but excessive anti-inflammatory responses may inadvertently impair immune-mediated wound healing and induce a state of immune insufficiency leading to a vulnerability to bacterial infection and increase the risk of hepatic decompenzation, as seen in patients with liver cirrhosis ( 34 ). A number of immune cells contribute to liver inflammation in CLD, including resident macrophages (KCs), infiltrating monocyte-derived macrophages, T cells, dendritic cell (DC)s and neutrophils.…”
Section: Inflammation In Chronic Liver Diseasementioning
confidence: 99%
“…In general, pro-inflammatory immune responses are thought to drive progressive CLD through bystander cell damage and activation of fibrogenic and hepatocarcinogenic pathways. Anti-inflammatory responses may counter these injurious pro-inflammatory responses and slow pathogenesis, but excessive anti-inflammatory responses may inadvertently impair immune-mediated wound healing and induce a state of immune insufficiency leading to a vulnerability to bacterial infection and increase the risk of hepatic decompenzation, as seen in patients with liver cirrhosis ( 34 ). A number of immune cells contribute to liver inflammation in CLD, including resident macrophages (KCs), infiltrating monocyte-derived macrophages, T cells, dendritic cell (DC)s and neutrophils.…”
Section: Inflammation In Chronic Liver Diseasementioning
confidence: 99%
“…Infections are more frequent among patients with SIRS and are importantly related to prognosis in cirrhosis [ 38 , 39 ]. Similarly, ACLF is a frequent complication of advanced cirrhosis, commonly triggered by infection, and strongly related to mortality [ 40 ]. Therefore, as observed for cirrhotics in general, among patients hospitalized for acute decompensation of cirrhosis who developed SIRS, the prognosis is related to the severity of the acute insult and presence of organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection has gained increasing attention in the study of liver failure because it not only could cause acute insult, inducing the occurrence of ACLF, but also tends to simultaneously occur at different sites in ACLF patients. [33][34][35] Further, infectious complication has been proven to accelerate the deterioration of ACLF, thus contributing to the exceedingly high mortality of ACLF patients. [36][37][38] Our study also confirmed the significantly increased mortality in patients with infection.…”
Section: Discussionmentioning
confidence: 99%